2016
DOI: 10.1021/acs.macromol.6b00011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics and Charge Transport in Polymeric Polyisobutylene-Based Ionic Liquids

Abstract: A homologous series of 16 polymeric ionic liquids (PIL) are investigated based on monovalent and bivalent telechelic polyisobutylene (PIB) carrying the ionic liquid (IL)-like cationic headgroup (N,N,N-triethyl­ammonium or 1-methyl­pyrrolidinium) and Br, NTf2, OTf, or pTOS as anions. Molecular dynamics, charge transport, and polarization at mesoscopic scales are analyzed over a wide frequency (10–2–107 Hz) and temperature (200–400 K) range by means of broadband dielectric spectroscopy (BDS); additionally, diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 51 publications
2
13
0
Order By: Relevance
“…Activation plot of both, structural relaxation rates (τ α : open symbols, τ β : filled symbols) for all four PAAPS-samples measured by BDS, as well as the dynamic glass transitions at various frequencies derived by ACC (open symbols with dots) and the calorimetric glass transition temperatures obtained by DSC (open symbols with cross).In addition, the structural relaxation rate (τmax) of the modified chemical structure PAPS (stars) is presented. The logarithm is to base 10; the error bars are smaller than the size of the symbols, unless otherwise indicated.The thermal activation of τ α follows a Vogel-Fulcher-Tammann temperature dependence leading to the assignment of this process to the dynamic glass transition; in accordance with the literature6,9,[17][18][19] tentatively originating from the relaxation of dipoles between mobile charge carriers.The secondary relaxation with relaxation time τ β is well separated and -within measurement accuracy -identical for all PAAPS samples. It appears at temperatures below 225K and follows an Arrhenius-law with a constant activation energy E β = 6 ± 0.5 · 10 −23 J = 0.37 ± 0.04 meV.…”
supporting
confidence: 83%
“…Activation plot of both, structural relaxation rates (τ α : open symbols, τ β : filled symbols) for all four PAAPS-samples measured by BDS, as well as the dynamic glass transitions at various frequencies derived by ACC (open symbols with dots) and the calorimetric glass transition temperatures obtained by DSC (open symbols with cross).In addition, the structural relaxation rate (τmax) of the modified chemical structure PAPS (stars) is presented. The logarithm is to base 10; the error bars are smaller than the size of the symbols, unless otherwise indicated.The thermal activation of τ α follows a Vogel-Fulcher-Tammann temperature dependence leading to the assignment of this process to the dynamic glass transition; in accordance with the literature6,9,[17][18][19] tentatively originating from the relaxation of dipoles between mobile charge carriers.The secondary relaxation with relaxation time τ β is well separated and -within measurement accuracy -identical for all PAAPS samples. It appears at temperatures below 225K and follows an Arrhenius-law with a constant activation energy E β = 6 ± 0.5 · 10 −23 J = 0.37 ± 0.04 meV.…”
supporting
confidence: 83%
“…First, cooling and heating affect the DC-conductivity by several orders of magnitude, as frequently observed for hopping transport. 25,31,32,73 Second, at the same temperature s 0 differs for different H-bond densities; a (by a factor of 3) greater density results in (20%) lower conductivity. Thus, for the particular case of PAAPS it is demonstrated that the thermal activation of molecular fluctuations affects the charge transport to a much greater extent than H-bonding.…”
Section: Resultsmentioning
confidence: 99%
“…29,[36][37][38] The dynamics of ion motion also appear to be strongly affected by the nanoscale structure of the materials, which can, depending on the polymer chemistry, separate into polar and nonpolar domains on the length scale of single monomers. 28,39,40 The successful application of BDS to this wide range of polymerized ionic liquid systems thus makes it an attractive technique for understanding the dynamics of ion motion in DPILs, as well.…”
Section: Introductionmentioning
confidence: 99%